Immersive Office 365 : bringing mixed reality and HoloLens into the digital workplace - Meijers, Alexander (Apress, 2020)
Bring mixed reality into your office workplace by building immersive experiences using data and content from your Office 365 platform. Imagine being able to sit at your desk and surround yourself with a 3D chart showing your work relationships as mined from your relationships with others based on how you collaborate together. This book shows you how to access your Office 365 data using the Microsoft Graph API, and then helps you present that data in a 3D modeling visualization using the Microsoft HoloLens 2 as a mixed reality device. This book covers the growing number of tools and techniques you can use to access and visualize data on a Microsoft HoloLens 2 device. Foremost is the Graph API, giving access to the full range of data in Office 365. Also covered are Unity and Visual Studio, the development environments from which you can create mixed reality applications for Microsoft HoloLens 2. You will learn how to load data from and save data to your Office 365 platform based on several interesting use cases. You will be able to extend your digital workplace into a 3D space powered by Microsoft HoloLens 2. Whether you know Office 365 and want to move toward mixed reality, or whether you know the Microsoft HoloLens 2 and want to build functionality around Office 365 data, this book helps you step up and accomplish your goal of bridging between mixed reality and Office 365. What You Will Learn Create immersive experiences using Microsoft HoloLens 2 and Office 365 Access Office 365 data programmatically using the Microsoft Graph API Control your immersive experiences using natural gestures and eye tracking Understand and correctly use different visualization models Implement design patterns to write better code in Unity Know how to access services using web requests via DLLs Who This Book Is For Developers who want to expand their knowledge of the Office 365 platform into the world of mixed reality by creating immersive experiences and 3D visualizations using the Microsoft HoloLens 2 and similar devices, and mixed reality developers who want to extend their repertoire toward serving everyday business needs of workers in corporate office environments.